2014
DOI: 10.3171/2014.3.focus1423
|View full text |Cite
|
Sign up to set email alerts
|

Less invasive surgery for treating adult spinal deformities: ceiling effects for deformity correction with 3 different techniques

Abstract: Object Minimally invasive surgery (MIS) options for the treatment of adult spinal deformity (ASD) have advanced significantly over the past decade. However, a wide array of options have been described as being MIS or less invasive. In this study the authors investigated a multiinstitutional cohort of patients with ASD who were treated with less invasive methods to determine the extent of deformity correction achieved. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…In our study, the maximum dSVA was 141.5 mm, which was greater than that previously reported. Other studies reported the maximum dLL and corrected LL by cMIS were 23°and 54°, respectively [25,26]. In our study, the maximum dLL and corrected LL were 67.5°a nd 62.4°, respectively, which were also greater than those of previous reports.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In our study, the maximum dSVA was 141.5 mm, which was greater than that previously reported. Other studies reported the maximum dLL and corrected LL by cMIS were 23°and 54°, respectively [25,26]. In our study, the maximum dLL and corrected LL were 67.5°a nd 62.4°, respectively, which were also greater than those of previous reports.…”
Section: Discussioncontrasting
confidence: 69%
“…The recent concept of cMIS is a combination of MIS lumbar interbody fusion and percutaneous fixation without osteotomy [3,[5][6][7][8]. Previously, cMIS was not indicated for sagittal correction of ASD [7,14,25,26]. Recent studies reported that cMIS could be indicated only for mild deformity, but osteotomies were required for marked deformity [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the observations of the International Spine Study Group (ISSG) that less invasive surgery for treating ASD have limitations for scoliotic-curve correction for advanced curves. 26 Overall, a minority of patients in each cohort experienced complications. Patients in the Open cohort experienced more dural tears and postoperative infections, while patients in the MIS cohort experienced greater postoperative radiating pain and need for revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Early results are promising, however, ASD patients with severe fixed sagittal imbalance and spinopelvic malalignment are not ideal candidates for MIS surgery alone [39,40]. The MIS approach remains in its early stage and work remains to produce more robust data with longer follow-up to make definitive claims regarding its efficacy and safety.…”
Section: Resultsmentioning
confidence: 99%